Design and Management of Digital Communication Media to Build Stakeholder Trust and Reputation of the Indonesian Ikaboga Organization - Pandjaitan, Rosmawaty Hilderiah; Gusfa, Henni; Wulandari, Ririn (Unram Journal of Community Service, 2024)
Ikatan Ahli Boga Indonesia (Ikaboga Indonesia) was established in 1987. It is the first and oldest organization for Indonesian Culinary Experts. This organization is neither commercial nor political. They are currently experiencing challenges such as the weak commitment of its members, especially in terms of setting aside time, energy, and materials. As a result, many organizational tasks are not carried out according to their duties. This organization is also weak in managing digital communication media. In the digital era, many organizations compete to build stakeholder trust and reputation through digital media. This is the background to this PKM. By paying attention to the three main principles of the SDGs, namely universal, integration, and inclusive, this PKM focuses on and aims to improve the skills (technology and management) of the administrators and members of Ikaboga Indonesia. Such as skills in organizational communication management and the design and management of digital communication media to build stakeholder trust and the reputation of Ikaboga Indonesia. This program is carried out by elaborating ten methods: learning methods, question and answer and discussion methods, demonstration methods, problem-solving methods, practice or skills training methods, design methods, discovery methods, inquiry methods, mind mapping methods, and role-sharing methods. As a result, this activity was positively influenced; 71% of participants attended because they were interested and wanted to learn. This PKM was also considered to impact 81.2% of participants' cognitive changes significantly. The causal factors did not have a 100% effect on increasing participants' cognitive abilities due to obstacles of 56.5% lost and intermittent sound due to signal.; 43.5% had a wrong signal.; 21.77% due to distance obstacles, and 17.4% due to technological barriers, hunger, and other work, so they could not focus.